PROFILE LEARNING STYLE UNTUK PENGEMBANGAN STRATEGI BELAJAR - Sumantri, Muh. Arief; Larasati, Ajeng Okvita; Hastuti, Wuryaning Hendri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2018)
Abstract.Learning styles are closely related to a person's person who is influenced by their nature,experience, education, and history of development.This study aims to find and describe Learning Styleowned by students. Type of research used is descriptive research using a quantitative approach.Population in this research is all postgraduate student psychology of Airlangga University of year2016/2017. Data analysis used is descriptive analysis method where from the data that have beencollected then classified in the form of numbers and declared in words in the form of sentence.The results showed that in general, students have a tendency of Visual and Auditory learning stylewhich has equal number and percentage of a 38%, then kinesthetic learning style with a percentage of24%.For male gender dominated by Auditory learning style with a percentage of 50%, women aredominated by Visual learning style with a percentage of 47%. In terms of specialization, community &Development Psychology concentration is dominated by learning style with percentage 67%, EducationalPsychology is dominated by Visual learning style with 46% percentage.Some of the benefits of understanding learning styles include maximizing learning potential,developing efficient and effective learning strategies, increasing self-esteemget insights into strengths andweaknesses, learn how to enjoy learning deeper, develop motivation to learn, and learn how to maximizeability and skills naturally.Keywords: Learning style, postgraduate student psychology